The Transformation and Evolution of Financial Reporting in Indonesia: A Historical Review and Its Manifestation in Financial Management - Retno Ryani Kusumawati; Rahmawati Rahmawati; Etty Puji Lestari; Julia Safitri (Journal of Comprehensive Science, 2026)
This research explores the historical development and transformation of financial reporting in Indonesia and its implications for financial management. Using a literature review approach, the research traces the evolution of reporting practices from colonial-era bookkeeping systems to the adoption of IFRS-based standards and the emergence of digital financial reporting. The findings reveal that changes in financial reporting represent more than technical or administrative adjustments; rather, they reflect a broader shift in the role of financial statements as instruments for internal decision-making and strategic financial control. This transformation is closely associated with several important regulatory milestones, including the establishment of the Ikatan Akuntan Indonesia (IAI), the issuance of Standar Akuntansi Keuangan (SAK), the convergence with International Financial Reporting Standards (IFRS), and the introduction of simplified standards such as SAK EMKM designed for micro, small, and medium-sized enterprises. This article contributes to academic discussions by conceptually linking financial reporting with managerial functions and by providing both theoretical and practical insights. In addition, it identifies opportunities for future empirical research, particularly concerning the effectiveness of financial reporting systems in supporting contemporary financial management practices